86.3k views
0 votes
Multiply the binomials and simplify so that they are in standard form. Show all your work.

(2x+5)(x-8)

User Llewey
by
5.6k points

2 Answers

0 votes

Answer:

2x² - 11x - 40

Explanation:

So we need to foil these two binomials

We need to take each term in the first binomial and multiply them by each term in the second binomial

It should look like this:

  • (2x)(x) + (2x)(-8) + (5)(x) + (5)(-8)

Then we can multiply each set of terms together to get:

  • 2x² + (-16x) + 5x + (-40)

Now we can get rid of the parenthesis:

  • 2x² - 16x + 5x - 40

Then we can combine like terms:

  • 2x² - 11x - 40

There is nothing more than can be done here so the final product is 2x² - 11x - 40

User Linguamachina
by
4.9k points
2 votes

Answer: The answer is = 2x^2 -11x-40

Step-by-step explanation: a= 2x, b=5, c= x, d =8

= 2xx + 2x (-8) + 5x +5(-8)

+ (-a)=-a

then simplify =2xx-2 -8x+5x.8

2xx=2x^2

2.8x=16x

5.8=40

=2x - 16x + 5x- 40

User Maurice Gilden
by
4.7k points